Bantuan Dana Usaha dan 1 Unit Motor Untuk Membantu Ekonomi Kesehatan Masyarakat Gowa - Pannyiwi, Rahmat; Zulham, Zulham; Rahmat, Rezqiqah Aulia; Kusumawati, Indra; Yusrianto, Yusrianto (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
UMKM are one of the UMKM businesses based on technology media in the production, distribution and consumption processes which apply family values in their transaction activities, both in the production, distribution and consumption processes. Digitalization of UMKM has become something that is inevitable, as well as an opportunity and challenge for the relatively large number of UMKM actors. The opportunity is to simplify the service process for UMKM activities, while the challenge is dealing with the lack of qualified human resources in digital-based UMKM businesses. The stages of implementing community service activities are carried out using the Participatory Rural Appraisal approach method and then providing assistance with 1 motorbike and additional capital for business partners. Based on the results of the community service activities above, it can be concluded that there is potential for competitive human resources oriented towards entrepreneurship and ownership in the Gowa area, Makassar City. There needs to be more attention to small and medium business actors in the context of developing entrepreneurship for them as a means of improving a better standard of living. Small and medium businesses must receive full support from the government so that small and medium businesses can develop further and also create greater job opportunities.